1989
DOI: 10.1145/66926.66932
|View full text |Cite
|
Sign up to set email alerts
|

CLASSIC: a structural data model for objects

Abstract: Abstractclassic is a data model that encourages the description o f o b j e cts not only in terms of their relations to other known objects, but in terms of a level of intensional structurea sw ell. The classic language of structured descriptions permits i partial descriptions of individuals, under an`open world' assumption, ii answers to queries either as extensional lists of valueso ra sd e s criptions that necessarily hold of all possible answers, and iiia n easily extensible s c hema, which can be accessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
2

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(72 citation statements)
references
References 15 publications
0
70
0
2
Order By: Relevance
“…We also showed that checking strong equivalence between two rules can be reduced into the logic of GK. Consequently, each rule base is strongly equivalent to a set of rules of form (3). Finally, we investigated the computational complexity in relation to this logic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also showed that checking strong equivalence between two rules can be reduced into the logic of GK. Consequently, each rule base is strongly equivalent to a set of rules of form (3). Finally, we investigated the computational complexity in relation to this logic.…”
Section: Resultsmentioning
confidence: 99%
“…In this section, we show that each rule base can be strongly equivalently transformed into a set of rules of form (3). The key technique of proving this is Theorem 11.…”
Section: Normal Forms Of General Default Logicmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently there have been efforts applying DL in the database field (Anwar, Beck, and Navathe, 1992;Borgida and Brachman, 1993;Beneventano, Bergamaschi, and Lordi, 1994;Borgida, Brachman, and McGuinness, 1989;Beck, Gala, and Navathe, 1989;Borgida, 1995;Bresciani, 1995;Bresciani, 1996;Bergamaschi, Lordi, and Sartori, 1994;Devanbu, 1993;Kessel, Rousselot, Schlick, and Stern, 1995), mainly because of the capabilities that are considered fundamental in semantic data modeling such as structural description and taxonomic classification (Hull and King, 1987) are inherently equipped within DL. Structural constructors pivotal within DL are concept, individual, and role where an individual represents a single object, a concept is a collection of individuals, and a role is a relation associating a pair of concepts or individuals.…”
Section: Description Logicmentioning
confidence: 99%
“…Inheritance relationships also arise in querying databases [2], and subsumption is used frequently in view management. Finally, knowledge representation systems allow concepts to be organized into subclass hierarchies, with inheritance being the key component of the reasoning algorithms [3].…”
Section: Introductionmentioning
confidence: 99%